Distributed, fixed‐time, and bounded control for secondary voltage and frequency restoration in islanded microgrids. Issue 2 (1st April 2019) - Shrivastava, Sonam; Subudhi, Bidyadhar
Abstract : Microgrid (MG) technology evolves as a promising solution to deal with the intermittent renewable generations and frequently changing load demand. This paper proposes a fully distributed and bounded secondary control algorithm with flexible convergence time for voltage and frequency restoration. It also enables accurate active power sharing for an islanded MG, compared with the well‐known consensus‐based distributed control approach. The proposed control scheme achieves accelerated fixed‐time convergence. The upper bound on the convergence is established by using the Lyapunov stability theory. The bounded, distributed control approach restores the voltage and frequency in fixed‐time while sharing the active power precisely. Further, the proposed controller is adaptive to the communication topology change and supports the plug and play feature of MG. Extensive simulations have been pursued using MATLAB/SimPowerSyetem toolbox considering frequent load perturbation and communication topology change. The obtained results are analysed to verify the performance of the proposed control algorithm. It is observed that the proposed bounded input controller converges faster than the conventional method.